EFEK POSTINGAN SARA DI MEDIA SOSIAL TERHADAP PERTEMANAN - Christine Purnamasari Andu (KRITIS : Jurnal Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2018)
AbstractThe research aims to know (1) the effects of post of ethnicity, religion, race and inter-group (SARA) at social media (2) ways to resolve the post of ethnicity, religion, race and inter-group (SARA) at social media. The research used qualitative descriptive methods. The research was conducted in Makassar city. Types and data sources used primary and secondary data. Primary data or main data which were taken form interview and secondary data supporting documents which were collected from books, dissertation, theses, journals, articles, and internet. There were 10 (ten) informants as samples were interviewed and the results of these interviews were analyzed using several theories. The research result indicate that (1) the post of ethnicity, religion, race and inter-group (SARA) at social media giving effects to friendship relations such as, several informants have chosen to limited their friendship relations to those who keeps continuing to post or share about ethnicity, religion, race and inter-group (SARA) issues although some of them will keep staying as a friend to keep their relations good. One of the informants said will limited herself to discuss with people who always post or share things about ethnicity, religion, race and inter-group (SARA). (2) Half of informants have chosen to just ignore about the post, some of them chose to delete those people from friend list at social media / erasing post / hiding post so that it will not show up at informants timeline and then one of the informants chose to reporting the post if its considered as an interference.